Association of frailty with health service utilisation and health care expenditure in sub-Saharan Africa: evidence from Côte d’Ivoire - Ambagtsheer, Rachel C.; Moussa, Richard K. (BMC, 2021)
Background: Frailty, a syndrome resulting in heightened risk of negative outcomes for older adults, is increasing across the globe. However, little is known about the health service impacts of frailty in low-income countries (LICs), and in particular, sub-Saharan Africa (SSA). This study explores the relationship between frailty and health service 1) utilisation and 2) expenditure within Côte d'Ivoire. Methods: Participants aged 50 years and over participated in the Living Condition, Health and Resilience among the Elderly study. Frailty was assessed using a 30-item Frailty Index (FI). The association between frailty and self-reported health service utilisation was analysed for general practitioners (GPs), specialists, overnight hospitalisations, traditional practitioners and self-medication. Expenditure over the previous month included consulting, medications, hospitalisations and total expenditure. Results: Among participants [n = 860, mean age (SD) = 61.8 (9.7) years, 42.9% female], 60.0% were frail, 22.8% pre-frail and 17.2% robust. The mean (SD) FI was 0.28 (0.17). Increased health service utilisation was associated with frailty for GP attendance, traditional practitioners and self-medication but not specialists or overnight hospitalisation. Pre-frailty and frailty were associated with increased total health service expenditure, with frailty also associated with aggregate consulting costs and medications. Conclusions: Although frailty is associated with health service utilisation and expenditure in a variety of contexts, the study results suggest that such impacts may vary across the globe. The experience of frailty in LICs is likely to differ from that experienced elsewhere due to cultural traditions, attitudes to the health system, and accessibility, with more research needed.
BMC Geriatrics, Volume 21
Keywords: (MESH); frailty; Aged; 80 and over; Health services; Africa south of the Sahara; École Nationale Supérieure de Statistique et d'Economie Appliquée d'Abidjan (ENSEA); Social/Econ Science